The Pass-Through of International Commodity Price Shocks to Producers’ Welfare : Evidence from Ethiopian Coffee Farmers - Kebede, Hundanol A. (World Bank, Washington, DC, 2021)
International commodity price shocks may have large impacts on producers in developing countries. In this paper, a unique household panel data from Ethiopia is utilize to show that a decrease in international coffee price has strong pass-through to the consumption of households that rely on coffee production as a main source of livelihood. It also results in decreases in on-farm labor supply (particularly male labor supply) and induces reallocation of labor towards non-coffee fields, but has negligible effect on off-farm labor supply. The decline in consumption has significant consequences on child malnutrition: children born in coffee-producing households during low coffee price periods have lower weight-to-age and weight-to-height z-scores than their peers born in non-coffee households.